Longitudinal flortaucipir accumulation is spatially distinct across baseline tau burden stages: Summary from three phase 2/3 interventional trials in Alzheimer's disease: Neuroimaging: Understanding tau progression. (7th December 2020) - Shcherbinin, Sergey; Higgins, Ixavier A.; Lu, Ming; Pontecorvo, Michael J.; Lo, Albert C.; Sims, John R.
Abstract: Background: To date, regional patterns of the longitudinal tau accumulation in Alzheimer's Disease (AD) have been examined in very few studies with limited sample sizes. We combined data from three phase 2 or 3 interventional trials to illustrate regional patterns of longitudinal flortaucipir accumulation. Method: EXPEDITION3 (NCT01900665), NAVIGATE‐AD (NCT02791191) and AMARANTH (NCT02245737) were double‐blind, placebo‐controlled multi‐center trials that enrolled amyloid‐positive patients with early or mild AD dementia. Longitudinal changes for flortaucipir were examined for N=208 placebo participants who underwent 8‐16 month follow‐up (scheduled or early discontinuation) flortaucipir scans. Flortaucipir scans were pooled across the three trials and divided into four stages corresponding to very low, low, medium, and high baseline global neocortical tau SUVR using pre‐determined cut‐points (Pontecorvo et al, 2019). A stage‐wise annualized percent change (APC) and mean‐standard deviation (SD) ratio (MSDR) of longitudinal tau accumulation were examined for 17 Automated Anatomical Labeling (AAL) atlas‐based bilateral cortical regions and a composite neocortical region of interest (ROI). Result: Our analysis suggested a dependence of the regional longitudinal tau accumulation profile on the global baseline tau burden at a group level. In the lowest baseline SUVR group (N=36), minimal accumulation was observed in the composite ROI (APC=0.04%, MSDR=0.01) and the inferior temporal region (APC=1.00%, MSDR=0.41) showed the strongest tau signal increase. At low (N=42) and medium (N=63) baseline levels, we found a relatively wide‐spread and spatially uniform accumulation with an APC of 2‐3% in the majority of the cortical regions and composite ROI. For patients with a high global baseline burden (N=67), tau increased in all considered frontal regions (APC ≥ 3.95%, MSDR>0.42) which exceeded accumulations in the composite ROI (APC=2.82%, MSDR=0.32). Conclusion: For the amyloid positive early‐to‐mild AD population, we found different cross‐sectional tau deposition and different regional longitudinal profiles across four baseline tau stages. Performing tau‐based screening might enroll more pathologically homogeneous populations in interventional trials and permit utilization of optimal measures of tau change as outcomes.